Evaluasi Green Building Berdasarkan Greenship pada Bangunan Gedung RSUD Grati Pasuruan - Qurrotus Shofiyah; Syahada, Virman (P4W IPB, 2024)
This research conducted focused on the Grati Hospital Building, which is an effort to mitigate global warming by evaluating the building in terms of green building principles. This is because the building is newly constructed and located in an industrial area with a dense population, making it suitable for a case study. The aim is to evaluate the RSUD Grati Hospital building based on the Green Building concept by applying Greenship assessment simulations. This research is classified as quantitative research, focusing on direct observational methods with reference to the Greenship Rating Tools, specifically version 1.2 for newly constructed buildings. The simulation results of the evaluation conducted on the RSUD Grati Hospital building are as follows: (1) Land Use Efficiency scores 7 points, (2) Energy Efficiency and Conservation scores 8 points, (3) Water Conservation scores 10 points, (4) Material Resources and Cycle scores 8 points, (5) Indoor Health and Comfort scores 6 points, (6) Building Environmental Management scores 4 points. Based on the points obtained, the overall rating is Bronze, with a score of 43 points or 42.57%, ranking fourth out of four ranks available, thus qualifying the building as a green building. The distinctive feature of the RSUD Grati Hospital building in implementing green building principles lies in its electricity and water conservation efforts, as reflected in the Energy Efficiency and Water Conservation categories.